Axial displacement model for reinforced concrete columns under lateral loading - Bicici, Erkan; Sezen, Halil (Elsevier Science Inc, 2026)
Recent major earthquakes have shown that reinforced concrete (RC) buildings with columns not meeting the seismic design and detailing requirements are susceptible to damage and collapse. For structural assessment and potential retrofit of existing RC buildings and for accurate modeling and analysis of columns in low to moderate seismic regions, it is essential to calculate the axial and lateral response accurately. Unfortunately, currently there is no established computational model to capture cyclic axial response of columns under lateral seismic loading. A novel axial model is proposed in this paper, which is integrated into dynamic lateral loaddisplacement analysis. This innovative model captures the cyclic axial displacement of RC columns, including typically overlooked axial softening behavior, which takes place after shear failure starts. The proposed model is based on the fact that the column axial stiffness decreases in parallel with lateral strength degradation beyond peak lateral strength. The innovative aspect of the model lies in accounting for axial-shear interaction by considering the variation of axial stiffness with respect to lateral displacement. The proposed model is validated by comparing the calculated response of test columns and frames with the experimental data. The new model is implemented in OpenSees software for dynamic analysis of frames to capture the additional column axial displacements due to axial softening as well as dynamic load redistribution within the frame structure.
Keywords: Axial-shear interaction; Reinforced concrete columns; Axial displacement; Column model; Column seismic response